(untitled) (Studia Prawnicze / The Legal Studies, 2023)
These considerations concentrate on the set of conditions affecting funda- mental methods of governing and shaping the attitudes of the members of hu- man community organized politically and subjected to the state power by the whole of elements forming the present sense of state of the society. The latter is understood as a specially qualified sense of a group of people relating to the content of the relationship of the society to a particular state structure and to the forms and methods of functioning of a state mechanism. In the content of this relationship conviction of the society (or of its basic part) concerning the real value’ and doubtless advantages of the existence of a state in social developement, in safeguarding material and spiritual needs of the citizens, in realization of moral and political ideas acknowledged and accepted by the society constitutes an element of considerable importance. We should also stress that such convic- tion and the estimation of the advantaged of the existence of state structures will not rely on model schemes but on the practice of political activity and on its results. The Author considers a truism statements such as these: that the sense of state is a historical category, a phenomenon subject to constant changes and re- volutionary leaps from quantitative to qualitative changes or that the evolution of the character of a state is connected with the changes of its social and poli- tical content. Thus the bigger is a group of persons having influence on political issues concerning their country and having the possibility to make fundamental decisions relating to the fate and to the future of the nation, the stronger and the more durable are the grounds of the present sense of state. Considerations presented in this essey are supposed to show among other things that not only class conditions influence the contents, the degree of intensity and te durability of the sense of state. Also in the countries where there is one and the same class, can we notice that this content differs in a higher or smaller degree. The following elements may be decisive: intensity of tradition and of the proper, centuries-long tradition, national composition of the society, the level of political culture, some features of the bottomless area of the social psyche and so on.